The Perception Of Esthetic And Mastication Functions Of Complete Denture In Elderly - Falatehan, Niko; Fahira, Jihan (Cakradonya Dental Journal, 2020)
Complete tooth loss is a common dental and oral health problems suffered by elderly. Prosthodontic treatment such as complete denture may overcome those problems.The perception of elderly in theuseofcomplete denture is important to evaluate the advantages and disadvantages ofthe complete denture, especially in terms of esthetics and mastication. This study aims to identify the perception of elderly in esthetic and mastication functions of complete denture. This study is descriptive observational with cross-sectional design conducted on 30 elderlies at Panti Werdha Tresna Wisma Mulia, Jelambar, West Jakarta. The Oral Health Impact Profile (OHIP-14) measures the perception of elderly in esthetic and mastication functions of completedenture.Analysis test using SPSS program for windows version 22.0showed that overall sample has moderate perception of esthetic and mastication functions of complete denture. Based on gender, the men group with moderate category have perception about the mastication function of complete denture that is equal to 84, 6%, while women group with good categoryhaveperceptionaboutestheticsfunctionofcompletedenturethatis equal to 58,8%. Men are more concerned with the mastication function, while women are more concerned with esthetic function in the use of complete denture.